Compensatory Financing Facility. (Pamphlet Series, 1980)
This paper examines compensatory financing facility in the IMF. Compensatory financing facilities are easy to administer and can give immediate relief to primary exporting countries when their export earnings fall. The IMF's compensatory financing facility was established in 1963, but only 57 drawings, totaling SDR 1.2 billion, were made during its first 13 years. A turning point was the liberalization of the facility in December 1975, which occurred when commodity prices were at their trough because of the severe recession in 1975. From January 1976 to March 1980, there were 107 drawings totaling SDR 4.0 billion under the facility.